Kepatuhan Pemilik Restoran Terhadap Peraturan Daerah Kota Bandung Nomor 20 Tahun 2011 Tentang Pajak Daerah (Wilayah Kerja Unit Pelayanan Pajak Bandung Utara) - Kristian Widya Wicaksono (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2019)
In Bandung, regional regulations relating to local tax are stated in the Regional Regulation Number 20 of 2011. Restaurant tax is a part of the local tax which has a promising impact to increase local government income. Restaurant tax administration is a series of activities ranging from planning, collecting to controlling. The purpose of this study is to explore the compliance of restaurant owners in the northern region of Bandung City with Regional Regulation No. 20 of 2011. To measure the level of compliance, the authors used three aspects namely regulatory knowledge, willingness to comply and the ability to comply. The urgency of this research is to find the facts behind the violations committed by some restaurant owners. The approach of this research is qualitative research. In addition, the author uses case studies as a research design. Data were obtained through interviews, field observations, and document studies and the researchers analyzed it by using qualitative data analysis methods introduced by Miles and Huberman. The results of this study shows that restaurant owners in the northern part of Bandung City do not fully comply with the restaurant tax payment mechanism because they do not know information about the requirements for tax payments due to passive Regional Government socialization of restaurant taxes and the number amount of tax is overburdened. Therefore, the burden becomes a market disincentive for restaurant owners coupled with the atonic tax controlling carried out by Local Government Agencies (Disyanjak).